(untitled) (Research, Society and Development, 2022)
To identify in the scientific evidences the interventions of nurses to prevent noncommunicable chronic diseases in the primary health care. Method: this is an integrative review whose database / data library used were Institute for Scientific Information - (ISI Web of Sciencetm, Database of Nursing (BDENF), Scientific Electronic Library Online (SciELO). The data collection occurred in September and October of 2018 using controlled and uncontrolled descriptors crossed between them by the Boolean operators OR and AND. The sample was 6 articles. The data were collected through the collection instrument validated by Ursi and grouped in flow charts and synoptic charts. The main interventions evidenced in the literature were nursing consultation, pap smear collection, clinical examination of the breasts, mammography, self-examination of the breasts, active search of users with suspicious reports of malignancy, lectures, groups, guidelines, counseling, and among the tools used are: the use of computerized systems, basic care notebooks, specific, guidelines. The evidence show that the strategies most used in the prevention of noncommunicable chronic diseases in Primary Health Care are related to the practice of preventing / controlling and tracking cancer.